2017
DOI: 10.5943/cream/7/4/1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and diversity of the fruticose lichen Usnea in Kalinga, Luzon Island, Philippines

Abstract: The mountains of Kalinga are home to countless unprecedented organisms. Its cool temperature and high elevation provide the perfect niche for such organisms to survive and these include the lichens. Kalinga harbors a wide variety of lichens stretching from crustose, foliose and fruticose types. Interestingly, the genus Usnea is one of the most commonly found fruticose lichens in the northern part of the Philippines. However, these organisms remain neglected and hence limited studies have been document. In fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Usnea hirta is one of the presumably most widespread species in the genus with reports from all major areas in North and South America, Europe, Africa, Asia, and Oceania (Mies 1989;Halonen et al 1998;Elix & McCarthy 1998Fos & Clerc 2000;Calvelo & Liberatore 2002;Articus et al 2002;Bjerke et al 2006;Clerc 2007;Randlane et al 2009;Kelly et al 2011;Saag et al 2011;Shrestha et al 2012;Noer et al 2013;Santiago et al 2013;Myllys et al 2014;Burkin & Kononenko 2015;Shukla et al 2015;Herrera-Campos 2016;Paliya et al 2016;Gagarina et al 2017;Galinato et al 2017Galinato et al , 2018Bungartz et al 2018;Esslinger 2019). All accessions in this strongly supported clade were from Europe (Articus et al 2002;Kelly et al 2011;Saag et al 2011;Millanes et al 2014;Araujo 2016).…”
Section: Usnea Subgenus Neuropogon New Zealand Cladementioning
confidence: 99%
See 4 more Smart Citations
“…Usnea hirta is one of the presumably most widespread species in the genus with reports from all major areas in North and South America, Europe, Africa, Asia, and Oceania (Mies 1989;Halonen et al 1998;Elix & McCarthy 1998Fos & Clerc 2000;Calvelo & Liberatore 2002;Articus et al 2002;Bjerke et al 2006;Clerc 2007;Randlane et al 2009;Kelly et al 2011;Saag et al 2011;Shrestha et al 2012;Noer et al 2013;Santiago et al 2013;Myllys et al 2014;Burkin & Kononenko 2015;Shukla et al 2015;Herrera-Campos 2016;Paliya et al 2016;Gagarina et al 2017;Galinato et al 2017Galinato et al , 2018Bungartz et al 2018;Esslinger 2019). All accessions in this strongly supported clade were from Europe (Articus et al 2002;Kelly et al 2011;Saag et al 2011;Millanes et al 2014;Araujo 2016).…”
Section: Usnea Subgenus Neuropogon New Zealand Cladementioning
confidence: 99%
“…It must be noted that, while the available sequence data originated from Europe and Africa, Usnea articulata is regarded as a cosmopolitan species ( Fig. 18; Swinscow & Krog 1976aElix & McCarthy 1998Stevens 1999;Clerc 2007Galloway 2007;Randlane et al 2009;Schumm & Aptroot 2010;Gumboski & Eliasaro 2011;Kelly et al 2011;Saag et al 2011;Ohmura 2012;Orock et al 2012;Schoch et al 2012;Truong et al 2013a, b;Millanes et al 2014;Rafat et al 2015;Nadel 2016;Galinato et al 2017;Lücking et al 2020c). The sequenced African samples already indicated that U. articulata s.lat.…”
Section: Usnea Subgenus Neuropogon New Zealand Cladementioning
confidence: 99%
See 3 more Smart Citations